Surgical outcomes of video-assisted neck surgery for papillary thyroid carcinoma - Misaki, Mariko; Inoue, Seiya; Kawakita, Naoya; Takeuchi, Taihei; Miyamoto, Naoki; Sakamoto, Shinichi; Fujiwara, Satoshi; Goto, Masakazu; Tsuboi, Mitsuhiro; Toba, Hiroaki; Takizawa, Hiromitsu (Surgery today (Tokyo, Japan), 2025)
Purpose New approaches to endoscopic thyroid surgery have been developed to improve cosmetic results, one of which is video-assisted neck surgery (VANS). The present study investigates the safety and effectiveness of thyroidectomy by VANS as oncologic surgery for papillary thyroid carcinoma (PTC). Methods The subjects of this retrospective study were 121 patients with PTC, who underwent hemi-thyroid lobectomy and central lymph node dissection via open surgery ( n = 102) or VANS ( n = 19) at Tokushima University Hospital between 2011 and 2023. We performed 1:1 propensity score matching and then compared the surgical outcomes between the two matched groups. Results Propensity score matching generated 18 distinct examination pairs. The VANS group had significantly less blood loss ( P = 0.003), but a longer operative time ( P < 0.001) than the open thyroidectomy group. There were two cases of transient recurrent laryngeal nerve paralysis and one case of recurrence in the lateral regional lymph nodes in the VANS group. However, no significant differences were observed in the incidence of complications ( P = 0.243) or recurrence ( P = 0.500) between the two groups. Conclusion VANS is a safe and effective surgical procedure for PTC, but longer follow-up is needed to assess tumor recurrence.